2021
DOI: 10.3390/pathogens10091191
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Viral Transmission and Evolution of Bovine Leukemia Virus through Long Read Oxford Nanopore Sequencing of the Proviral Genome

Abstract: Bovine leukemia virus (BLV) causes Enzootic Bovine Leukosis (EBL), a persistent life-long disease resulting in immune dysfunction and shortened lifespan in infected cattle, severely impacting the profitability of the US dairy industry. Our group has found that 94% of dairy farms in the United States are infected with BLV with an average in-herd prevalence of 46%. This is partly due to the lack of clinical presentation during the early stages of primary infection and the elusive nature of BLV transmission. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…The reads obtained were reference assembled against the known MCP phaeoviral genes (McKeown et al, 2017) using Minimap 2.17 in Geneious Prime 2021.1.1 and manually curated to correct ambiguities where possible. Fidelity of the PCR plus ONT approach was previously confirmed using a bovine leukemia virus model (Pavliscak et al, 2021).…”
Section: Phaeoviruses Found In Recovering Nereocystis Luetkeana Kelp ...mentioning
confidence: 93%
“…The reads obtained were reference assembled against the known MCP phaeoviral genes (McKeown et al, 2017) using Minimap 2.17 in Geneious Prime 2021.1.1 and manually curated to correct ambiguities where possible. Fidelity of the PCR plus ONT approach was previously confirmed using a bovine leukemia virus model (Pavliscak et al, 2021).…”
Section: Phaeoviruses Found In Recovering Nereocystis Luetkeana Kelp ...mentioning
confidence: 93%
“…DNA quantity and quality was determined using the NanoDrop One/One c (ThermoFisher Scientific, Austin, TX, USA). The methods to determine PVL followed Pavliscak et al, 2020 [ 24 ], and PVL was reported as a ratio of BLV polymerase gene copies to Beta Actin gene copies.…”
Section: Methodsmentioning
confidence: 99%
“…Animal virus infections can spread rapidly and have severe socioeconomic consequences. Nanopore sequencing has been used to identify various animal viruses, including differentiating between three Capripox Viruses in outbreaks in the Middle East and Africa, 277 identifying African horse sickness in an outbreak in Thailand, 278 and tracking Enzootic Bovine Leukosis caused by Bovine leukemia virus transmission in US pastures 279 . It has also been used to reveal the complex transcriptional landscape of porcine reproductive and respiratory syndrome virus 280 …”
Section: Applications Of Nanopore Sequencing In Other Microbial Detec...mentioning
confidence: 99%